2018
DOI: 10.1159/000493401
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Defects in the Cellular DNA Damage Response for the Treatment of Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic cancer is one of the most common causes of cancer-related mortality in the Western world and pancreatic ductal adenocarcinoma (PDAC) is by far the most common pancreatic cancer entity. Locally advanced or metastatic PDAC remains a major clinical challenge, and the prognosis of affected patients is dismal despite substantial research efforts in this area. Recent large-scale genomic analyses of PDAC revealed that KRAS is the most frequently mutated driver gene in this entity. In addition, a relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 93 publications
(210 reference statements)
0
3
0
Order By: Relevance
“…Herein, we also evidenced that CBD and O 2 /O 3 , as single treatment or in combination, are able to reduce the expression of different genes of the PI3K pathway. PDAC, as above described, is also characterized by the acquisition of an anti-apoptotic phenotype, partially by inhibition of p53 and over-expression of anti-apoptotic proteins, which correlate with short survival and overall survival, particularly in Bcl-2 positive cases [ 55 , 56 ], and mutation in genes related to DNA damage response, such as BRCA1/2 [ 54 , 57 ]. Herein, we showed that CBD alone increased p53 and reduced BRCA2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we also evidenced that CBD and O 2 /O 3 , as single treatment or in combination, are able to reduce the expression of different genes of the PI3K pathway. PDAC, as above described, is also characterized by the acquisition of an anti-apoptotic phenotype, partially by inhibition of p53 and over-expression of anti-apoptotic proteins, which correlate with short survival and overall survival, particularly in Bcl-2 positive cases [ 55 , 56 ], and mutation in genes related to DNA damage response, such as BRCA1/2 [ 54 , 57 ]. Herein, we showed that CBD alone increased p53 and reduced BRCA2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…For all this molecular evidence, ATM status analysis displays clinically relevant therapeutic implications. Indeed, similar to BRCA genetic alterations, ATM aberrations increase the efficacy of chemotherapeutic drugs which induce double strand DNA breaks, such as platinum drugs [67,68].…”
Section: Colloid Carcinomamentioning
confidence: 99%
“…Several genetic predispositions and molecular alterations (31) have been found to be associated with this highly lethal entity. The most common mutated oncogenes in PAC and that were among the first to be reported in the literature are KRAS (32) and Bcl-2 (21), while p53 (33)(34)(35), deleted in pancreatic cancer 4 (21), cyclin-dependent kinase inhibitor 2 (CDKN2A) (17,35,36), retinoblastoma protein (17,21,33,34,36) are the most frequently deleted tumor suppressor genes. CDKN2A is a gene that encodes proteins involved in regulating the cell cycle, and mutations in this gene are commonly detected in PAC (36).…”
Section: Introductionmentioning
confidence: 99%